Application of the new classification proposal for juvenile idiopathic arthritis of the pediatric rheumatology international trials organization in a group of Mexican patients - Ramos-Tiñini, Pamela; Menchaca-Aguayo, Héctor; Alpizar-Rodriguez, Deshire; Mercedes-Pérez, Esther; Faugier-Fuentes, Enrique (Frontiers in Pediatrics, 2024)
Objective: Apply the PRINTO classification proposal for diagnosing Juvenile Idiopathic Arthritis (JIA) to Mexican patients, analyzing demographic, clinical, and laboratory characteristics. Material and Methods: Cross-sectional study analyzing patients diagnosed with JIA using International League of Associations for Rheumatology (ILAR 2001) criteria over two years at a national rheumatic disease center. Reclassification was done using the Pediatric Rheumatology International Trials Organization (PRINTO) proposal. Comparisons were made between antinuclear antibodies (ANAs) positive versus negative and rheumatoid factor (RF) positive versus negative patients. Results: Seventy-six patients were analyzed, mostly female. Median age was lower in systemic JIA (sJIA) and early onset JIA with positive ANAs (eoANA JIA). ANAs was present in 78.6% of patients. Reclassification according to PRINTO disorders showed RF positive polyarticular JIA, sJIA, and enthesitis-related JIA (ER JIA) reclassified to RF JIA, sJIA, and enthesitis/spondylitis-related JIA (ESR JIA) by 100%, 94.7%, and 80%, respectively. The ILAR category with the most variation was RF negative polyarticular JIA. Early disease onset was associated with a lower probability of positive RF after adjusting for sex, age, and ANAs. No association was found between ANAs positive versus negative in adjusted multivariate analysis. Conclusions: We found compatibility of sJIA, RF positive polyarticular JIA, and RE JIA categories with sJIA, RF JIA, and ESR JIA disorders, respectively. Differences were noted in variables such as sex and the number of affected joints. There was high ANAs positivity; however, few patients were classified into eoANA JIA disorder, with only one presenting uveitis. Most patients were classified as other JIA.